Cytomorphological spectrum and Ziehl-Nelson staining in suspected tuberculous lymphadenitis: A study of 100 cases. - Dhawan, Indrani; Gupta, Oneal; Kaushik, Ankit; Ranga, Sunil; Kasana, Dimple; Gupta, Prem Kumar (Annals of Pathology and Laboratory Medicine, 2015)
Background:Â  Tuberculosis (TB) is the leading cause of death from a curable infectious disease. The situation is further worsened by a resurgence of the disease in immunocompromised AIDS cases. Lymphadenitis is the most frequent form of extrapulmonary tuberculosis. The diagnosis of tuberculous lymphadenitis remains challenging in spite of the availability of various diagnostic tools. Aims: The present study aims at studying different cytomorphological patterns in suspected cases of tuberculous lymphadenitis and the efficacy of cytology and Ziehl-Nelson (ZN) staining in diagnosing tuberculous lymphadenitis in these different patterns. Methods: One hundred cases clinically suspected of tuberculous lymphadenitis were studied (over a period of one year) with the aid of fine needle aspiration cytology (FNAC) complemented with AFB staining. The cytomorphological spectrum along with AFB positivity in different groups was compared. Results: Maximum AFB positivity was seen in cases showing cytomorphological features consistent with a granulomatous lesion with necrosis (i.e. in 10 out of 21 cases; 48%). The difference in AFB positivity between various cytomorphological groups was found to be statistically significant (p < 0.01) especially between cases showing caseating granuloma and those showing non-caseating granuloma or reactive lymphadenitis at 1% level of significance. The maximum sensitivity of ZN stain was found in cases showing caseating granuloma, and was nil in cases showing non-caseating granuloma and cases showing reactive lymphadenitis. Conclusion: The maximum AFB positivity is seen in cases showing cytomorphological features consistent with a granulomatous lesion with necrosis.Â  A combination of conventional techniques (FNA and ZN staining for AFB) and newer diagnostic techniques must be applied for the rapid and early diagnosis of tuberculosis in paucibacillary specimens to achieve maximum sensitivity.